2016
DOI: 10.1371/journal.pone.0158863
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Killer Cell Receptors and Cytotoxic Activity in Phosphomannomutase 2 Deficiency (PMM2-CDG)

Abstract: BackgroundPMM2-CDG is the most common N-glycosylation defect and shows an increased risk of recurrent and/or severe, sometimes fatal, infections in early life. We hypothesized that natural killer (NK) cells, as important mediators of the immune response against microbial pathogens and regulators of adaptive immunity, might be affected in this genetic disorder.ObjectiveTo evaluate possible defects on PMM2-CDG NK peripheral blood cell number, killing activity and expression of membrane receptors.MethodsWe studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…Our study confirmed previously reported infection-related features in PMM2-CDG, namely (1) the higher prevalence of infections during infancy/early childhood; (2) their organ-specific pattern (particularly RT and GI); (3) the not negligible occurrence of sepsis evolving from organ-specific infections and iv) their associated early lethality [ 13 , 14 , 16 , 17 , 52 , 53 ]. All these observations highlight the need for close monitoring until full remission occurs to ensure recovery and to prevent clinical aggravation and fatal outcomes [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study confirmed previously reported infection-related features in PMM2-CDG, namely (1) the higher prevalence of infections during infancy/early childhood; (2) their organ-specific pattern (particularly RT and GI); (3) the not negligible occurrence of sepsis evolving from organ-specific infections and iv) their associated early lethality [ 13 , 14 , 16 , 17 , 52 , 53 ]. All these observations highlight the need for close monitoring until full remission occurs to ensure recovery and to prevent clinical aggravation and fatal outcomes [ 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…Immunological involvement in CDG is an underexplored field. Even though the ubiquitous importance of glycans in the immune system and response is well-established, clear molecular and clinical evidence capable of fully clarifying the immune phenotype of CDG patients, particularly in PMM2-CDG, is lacking [13,14,16,17,[50][51][52]. This lack of knowledge regarding immunological involvement is evidenced in this study by: (i) the~11% of PMM2-CDG patients with unsolved immune status and (ii) the uncertainty or ignorance of PMM2-CDG participants about the presence of specific immune-related manifestations (6.6%, 7.4% and 16.4% related to allergies, infections and autoimmune diseases, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In two patients, fever was also associated with pericarditis and vasculitis . Half of the patients reported responded normally to vaccination . Age‐appropriate vaccination is recommended …”
Section: Systems Summaries and Statementsmentioning
confidence: 99%
“…The spontaneous closure of ASD is a very complicated process and the mechanism is still unclear, it is generally believed that low weight gain with growth retardation, persistent continuous blood shunting, and delayed development of the cardiac septum may affect this process, causing the exacerbation of ASD [ 13 ]. Immune dysfunction and failure to thrive are both common in patients with CDG-1a [ 14 ]. In our patient, immune dysfunction and failure to thrive occurred at an early stage and persisted in the whole course of the disease.…”
Section: Discussionmentioning
confidence: 99%